Minor histocompatibility antigens as determinants for graft‐versus‐host disease after allogeneic haematopoietic stem cell transplantation. (11th March 2013) - Turpeinen, H.; Ojala, P. J.; Ojala, K.; Miettinen, M.; Volin, L.; Partanen, J.
Summary Minor histocompatibility antigens (minor H antigens) are genetically polymorphic peptides that have been shown to elicit immune response when mismatched between donor and recipient of haematopoietic stem cell transplantation (HSCT). Depending on the expression profiles, mismatches in these genes may either lead to harmful graft‐versus‐host (GvH) reaction or desired graft‐versus‐leukaemia (GvL) effect. We analysed retrospectively the effect of HLA‐restricted matching 11 established autosomal minor H antigens on the risk of graft‐versus‐host disease and relapse in 311 HLA‐matched sibling HSCT of a single centre. Increased incidence of chronic GvH disease was shown to be associated with mismatches in the HA‐8 and ACC‐1. The mRNA expression profiles in a large set of healthy and malignant tissue samples of minor H antigen genes demonstrated in silico that the expression profiles of HA‐8 and ACC‐1 were surprisingly different: HA‐8 gene was expressed in practically all tissues, whereas ACC‐1 gene had a restricted profile. The results demonstrated that mismatches in minor H antigens HA‐8 and ACC‐1 predisposed to chronic graft‐versus‐host disease (GvHD).